Synthesis of 2-Thiophenyl-3-Substituted Phenyl-4-Oxo-5-Substituted Benzylidine Thiazolidine - Idrees, Mohd.; Siddique, Mohd.; Doshi, A.G.; Raut, A.W. (Asian Journal of Chemistry, 2010)
4-Thiazolidinones are known for their antibacterial, antifungal, antithyroid and amoebicidal properties. 2-Thiophenyl-3-substituted phenyl-4-oxo-thiazolidines were condensed with aromatic aldehyde (benzaldehyde, anisaldehyde, salicylaldehyde and 2-nitrobenzaldehyde) to yield 2-thiophenyl-3-subsituted phenyl-4-oxo-5-substituted benzylindine-thiazolidine. The structures of these compounds were confirmed by spectral and chemical data.